Dual Spaces of Multiparameter Local Hardy Spaces - Wei Ding; Feng Yu (Journal of Function Spaces)
In this paper, we study the duality theory of the multiparameter local Hardy spaces hpℝn1×ℝn2, and we prove that hpℝn1×ℝn2∗=cmopℝn1×ℝn2, where cmopℝn1×ℝn2 are defined by discrete Carleson measure. Moreover, we discuss the relationship among cmopℝn1×ℝn2, Lippℝn1×ℝn2, and rectangle cmorectpℝn1×ℝn2.